Personality traits and job performance : an empirical analysis at Malakoff Corporation Berhad / Nur Syahirah Zahari - Zahari, Nur Syahirah (2015)
This research consists of the empirical analysis on the big five personality traits and the relationship towards job performance at Malakoff Corporation Berhad. Personality traits influence occupational choice and are valid predictors of managerial success. The primary objective of this study was to investigate whether a relationship exists between possessing certain personality traits and employee job performance. The personality dimensions of the five factor model of personality, Conscientiousness, Agreeableness, Neuroticism, Openness To Experience and Agreeableness were the focus of this study. The type of research is correlational research. Simple random sampling was employed and a measuring instrument distributed to the respondents, in which 148 questionnaires were returned. An exploratory factor analysis was undertaken and Cronbach Alpha coefficients calculated to assess the validity and reliability of the measuring instrument. Descriptive statistics were calculated to summarize the sample data. Pearson correlation analysis was undertaken to establish relationships between the independent variable (the five dimensions of personality) and the dependent variable, job performance. The findings of this study show that individuals who have high levels of the personality traits of extraversion, conscientiousness sand agreeableness are more likely to perform better.